Investment Analysis of Heavy Equipments for Cut and Fill Work on Toll Road Construction Project : (Case Study: Trans Sumatra Toll Road Section 3, Bakauheni-Terbanggi Besar) - Kustiani, Ika; Syahputra, Reyzanza Anandio; Dasaputra, Andius (Journal of Engineering and Scientific Research, 2025)
Toll roads are vital infrastructure; however, their construction requires significant capital expenditures. One significant cost component is the cost of heavy equipment. The investment schemes considered in this study are cash new purchase, leasing, and rental. The best investment decision requires engineering investment analysis, including the NPV, IRR, BCR, and PP methods. The estimated cost of owning heavy equipment with a cash scheme is Rp 46.06 billion, a leasing scheme is Rp 53.50 billion, and a rental scheme is Rp 66.66 billion. The operating cost for all schemes is the same, amounting to Rp 56.44 billion during the construction period. The financial analysis results show that the cash scheme is the best with an NPV of Rp 9,198 billion, an IRR of 10.39%, a BCR of 1.12, and a PP of 3,3 years. Sensitivity analysis to interest rate increases shows that the cash scheme is feasible up to a 10% interest rate.